Beyond Orpheus: Studies in Musical Structure - Epstein, David (Cambridge, MI London MIT Press, 1980)
Examining the elements of musical structure and the ways they provide unity, coherence and uniqueness in classic-romantic music, the author defines the concept of Grundgestalt, or "basic shape" and follows its development from the music of the classic-romantic Viennese school to the twelve-tone compositions of Schoenberg.
Keywords: Musical analysis